Role of Medicinal Plants in Modern Medicine (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Medicinal plants have been used for centuries as a natural source of healthcare and continue to play a vital role in modern medicine. They contain a wide range of bioactive compounds, such as alkaloids, flavonoids, terpenoids, glycosides, and phenolic compounds, which possess therapeutic properties. Many modern drugs have been developed from medicinal plants, including aspirin from willow bark, paclitaxel from the Pacific yew tree for cancer treatment, digoxin from foxglove for heart diseases, and artemisinin from Artemisia annua for malaria. These plant-derived compounds have significantly contributed to the prevention and treatment of various diseases. Medicinal plants are widely used in pharmaceutical, nutraceutical, cosmetic, and traditional healthcare systems due to their effectiveness, accessibility, and natural origin. They also serve as an important source for discovering new drugs and developing safer therapeutic agents. With the increasing demand for natural and sustainable healthcare products, scientific research on medicinal plants has expanded to improve their quality, safety, and efficacy. However, challenges such as lack of standardization, overexploitation of plant resources, and quality control need to be addressed. Conservation of medicinal plant biodiversity and sustainable utilization are essential for future drug development. This review highlights the importance of medicinal plants, their role in modern medicine, major applications, advantages, challenges, and future prospects. Medicinal plants remain an invaluable resource for improving global healthcare and continue to inspire the discovery of innovative medicines for the treatment of various diseases.
Keywords: Herbal Medicine; Drug Discovery; Natural Products; Modern Medicine